Analisis Tren Komoditas Jagung di Jawa Timur - Wiratama, Hanan Kusuma; Prasetyo, Edy; Setiyawan, Hery (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Corn (Zea mays L.) is a strategic commodity in East Java, playing a crucial role in food security, feed industries, and the local economy. This study analyzed the trends in harvested area, production, and productivity of corn over the past 30 years (1994–2023) and examined the effect of harvested area on production. The results showed a consistent decline in harvested area, averaging 11,679 hectares annually, from 1,138,359 hectares in 1994 to 755,071 hectares in 2023. This decline was primarily driven by land-use changes for non-agricultural purposes and climate variability. Corn production, on the other hand, remained stable and increased from 3,041,768 tons in 1994 to 4,429,459 tons in 2023, supported by productivity improvements from 2.67 tons/ha in 1994 to 6.06 tons/ha in 2022. Forecasting up to 2028 projected a further decline in harvested area to 890,326 hectares, while production and productivity were expected to increase to 6,110,082 tons and 6.60 tons/ha, respectively. Regression analysis revealed a positive effect of harvested area on production, with a regression coefficient of 1.062. However, the contribution of harvested area was only 3% (R² = 0.03), indicating that other factors, such as agricultural technology and inputs, were more significant in determining production outcomes. This study highlighted the importance of protecting agricultural land, advancing technology adoption, and providing farmer training to maintain production stability. Policy support and diversification of corn-based products were also identified as critical strategies to enhance the sector’s competitiveness.